Role of knowledge and attitude in determining standard precaution practices among nursing students - Balami, Lawan Gana; Ismail, Suriani; Muhamad Saliluddin, Suhainizam; Garba, Sani Hyedima (Medip Academy, 2017)
Background: Standard precaution practice (SPP) is aimed at protecting both patients and health professionals alike. The high rate of occupational hazards among health workers especially in developing countries is counterproductive and therefore requires thorough investigation and intervention. This study aims to determine the role of knowledge and attitude in determining SPP among nursing students.